2009
DOI: 10.1186/1472-6904-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Methanol poisoning and long term sequelae – a six years follow-up after a large methanol outbreak

Abstract: Background: Mass poisonings with methanol are rare but occur regularly both in developed and in developing countries. Data from the poisoning episodes are often published, but follow-up-data is scarce. We therefore conducted a six year follow-up study after the large methanol outbreak in Estonia in September 2001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
70
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 15 publications
(21 reference statements)
7
70
0
4
Order By: Relevance
“…Methanol-induced optic neuropathy may resolve within a few weeks with complete recovery [10]. However, longterm visual sequelae may persist in up to 25-40% of patients [11][12][13].…”
Section: Importancementioning
confidence: 99%
“…Methanol-induced optic neuropathy may resolve within a few weeks with complete recovery [10]. However, longterm visual sequelae may persist in up to 25-40% of patients [11][12][13].…”
Section: Importancementioning
confidence: 99%
“…Even after a successful medical intervention and treatment, the future prognosis for these individuals is not good. This was well documented in a long-term follow-up of a mass methanol poisoning in Estonia (Paasma et al 2009). …”
Section: Discussionmentioning
confidence: 97%
“…The clinical symptoms of methanol poisoning include abdominal pains, nausea, visual disturbances and shallow breathing. The outcome seems to depend on the concentration of methanol in serum, the degree of metabolic acidosis and whether or not the patient was comatose or managed to hyperventilate and compensate for the metabolic acidosis (Paasma et al 2009). …”
Section: Pharmacodynamics Of Ethanolmentioning
confidence: 99%
“…To test this hypothesis, the affinity of abacavir for ADH in comparison with methanol should firstly be experimentally determined and if it is shown that it has a greater affinity for ADH compared with methanol, a multicenter randomized controlled trial study should be designed to compare fomepizole with abacavir in the treatment of methanol-poisoned patients. Albeit, the best opportunities for conducting this study are the mass poisonings with methanol that regularly occur in developed and developing countries [9,[18][19][20][21].…”
mentioning
confidence: 99%
“…In contrary, methanol poisoning is a rare toxicity that is seen in the form of isolated episodes and intentional ingestion, and sometimes occurs as single epidemies [9,[18][19][20][21]. Therefore, fomepizole is not widely stocked in some hospital pharmacy stocks in comparison…”
mentioning
confidence: 99%